2015
DOI: 10.1021/acs.jpca.5b07464
|View full text |Cite
|
Sign up to set email alerts
|

Ionization and Fragmentation of Formamide Induced by Synchrotron Radiation in the Valence Region via Photoelectron Photoion Coincidence Measurements and Density Functional Theory Calculations

Abstract: We have performed a theoretical and experimental study of the formamide (HCONH2) photofragmentation and photoionization processes in the gas phase. The experiment was perfomed by using a time-of-flight mass spectrometer using the photoelectron photoion coincidence (PEPICO) technique in the valence region, from photons with energy between 10 and 20 eV. We have obtained both mass and partial ion yield spectra, identified by the mass-to-charge ratio as a function of the photon energy. With this setup, we could as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 47 publications
(87 reference statements)
1
12
1
Order By: Relevance
“…We will show that while this is indeed the case, the A ̃+ state is not isolated and the dissociation is still statistical because the ground and first excited states are strongly coupled. Arruda et al reported the first photoelectron photoion coincidence experiment on the valence photoionization of formamide, 29 which, in the absence of internal energy selection by electron kinetic energy analysis, is in fact directly comparable to the previous photoionization mass spectrometry results. Indeed, the reported ionization onset and H loss, CO loss, and NH 2 loss appearance energies of 10.…”
Section: ■ Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…We will show that while this is indeed the case, the A ̃+ state is not isolated and the dissociation is still statistical because the ground and first excited states are strongly coupled. Arruda et al reported the first photoelectron photoion coincidence experiment on the valence photoionization of formamide, 29 which, in the absence of internal energy selection by electron kinetic energy analysis, is in fact directly comparable to the previous photoionization mass spectrometry results. Indeed, the reported ionization onset and H loss, CO loss, and NH 2 loss appearance energies of 10.…”
Section: ■ Introductionsupporting
confidence: 68%
“… a Thermochemical dissociative photoionization (Δ r H 0K ) energies are also given for comparison where relevant. This work’s calculations are average G4, CBS-APNO and W1U­(sc) results for minima and average G4 and W1U­(sc) results for transition states. b Literature values were taken from Leach et al c Literature values were taken from ter Steege et al d Literature values were taken from Arruda et al e Literature values were taken from Loudon and Webb f Literature values were taken from Schwell et al g Literature values were taken from Schröder et al …”
Section: Results and Discussionmentioning
confidence: 99%
“…1,10,11,16,17 The explanation found in the literature for these cations is generally due to the presence of the isotope 13 C. In a brief analysis by Leach et al 16 for the case of acetic acid, m/q = 60, it is suggested that the appearance of the ion at m/q = 61 can be due to the presence of an isotope 13 C, to the molecular fragmentation of dimers, or to the fragmentation of a complex formed by water contamination. According to this work, the formation energy of a protonated ion from a dimer would be about 200 meV lower than the ion derived from monomers containing 13 Aim of the present work is to analyze the process of protonation due to the formation of dimers and their influence on the results of molecular ionization and fragmentation pattern at VUV range.…”
mentioning
confidence: 99%
“…In previous studies of the photofragmentation of formic acid and formamide in the valence region, we observed the production of a protonated ion, with a mass-to-charge ratio one unit larger than the parent ion. In a recent work we investigated the protonation process of double deuterated formic acid (DCOOD) as a result of dimers photofragmentation in the valence region .…”
Section: Introductionmentioning
confidence: 83%
“…This beamline has a monochromator with spherical diffraction gratings, which selects photons with energies between 250 and 1000 eV and energy resolution of E /Δ E = 1000, for 100 μm slits. The spectrometer allows to collect the PEPICO and PEPIPICO techniques. , The PEPICO and PEPIPICO spectroscopy has been widely used in recent studies , to determine the fragmentation pathways of different molecular species that are single and doubly ionized.…”
Section: Technical Detailsmentioning
confidence: 99%